Ecological and economic system: concepts and structure - Кузьменко, О. К. (Scientific Progress & Innovations, 2012)
A category of ecological and economic system, as integrity of the ecological and economic systems, which is characterized intensity of internal communications and emergent properties. The analysis of structural elements of the ecological and economic system is conducted. The scheme of co-operation of constituents of the ecological and economic system is offered with a glance influence by agricultural enterprises.